Emotion regulation and emotional distress: The mediating role of hope on reappraisal and anxiety/depression in newly diagnosed cancer patients. Issue 8 (24th October 2016) - Peh, Chao Xu; Liu, Jianlin; Bishop, George D.; Chan, Hui Yu; Chua, Shi Min; Kua, Ee Heok; Mahendran, Rathi
Abstract: Purpose: A proportion of newly diagnosed cancer patients may experience anxiety and depression. Emotion suppression has been associated with poorer psychoemotional outcomes, whereas reappraisal may be an adaptive emotion regulation strategy. Few studies have examined potential mechanisms linking reappraisal to psychoemotional outcomes in cancer patients. This study aims to replicate findings on reappraisal and suppression and further examines if hope mediates the association between reappraisal and anxiety/depression in patients newly diagnosed with cancer. Methods: Participants were 144 adult cancer patients (65.3% female, mean age = 48.96 years, SD = 9.23). Patients completed a set of study questionnaires, including the Emotion Regulation Questionnaire, Adult Hope Scale, and the Hospital Anxiety and Depression Scale. Path analysis was used to examine if hope mediated the association between reappraisal and anxiety/depression. Results: Prevalence of anxiety was 39.6% and depression was 25.0%. Reappraisal and hope were correlated with lower anxiety and depression, whereas suppression was correlated with higher anxiety and depression. The hypothesized mediation model provided fit to the data, comparative fit index = 0.95, Tucker‐Lewis index = 0.94, root‐mean‐square‐error of approximation = 0.05. There was a significant indirect effect of reappraisal on anxiety and depression via hope, b  = −0.95, SE = 0.42, 95% confidence interval = −1.77 to −0.12, whereas the direct effect of reappraisal was nonsignificant. Conclusion: The study findings suggest that hope mediated the association between reappraisal and anxiety/depression outcomes. Moreover, the high prevalence of anxiety and depression implies a need for healthcare providers to attend to the psychoemotional needs of newly diagnosed cancer patients.